The Correlation between Thyroid Hormone Levels with Functional Mobility Performance among the Geriatric Patients in Dr. Sardjito General Hospital - Henny Rumaropen; M Robikhul Ikhsan; Raden Bowo Pramono (Acta Interna The Journal of Internal Medicine, 2020)
Background. Alteration of the endocrine system in the elderly people may be caused by changes in secreted hormone levels or decreased sensitivity of target organs. These changes also apply to thyroid function, which can cause disability, cognitive impairment, cardiovascular risk, and decreased muscle mass and strength in the elderly. Physiologically, there are several changes in the concentration of thyroid hormone Concentrations due to aging process, such as reduced TSH (Thyroid Stimulating Hormone), total T3 (Triiodothyronine) and free T levels, and increased rT3 (Reverse triiodothyronine), which is an inactive T (Thyroxine) metabolite in the serum. Even so,the free T4 and the total T44 remain unchanged, except for the sick. As a result, proper diagnosis and management are expected to minimize the deprivation experienced by the subjects due to a decrease in functional mobility.Aims. The aim of the study was to assess the correlation between the levels of thyroid hormones and functional mobility among the elderly at Dr. Sardjito General Hospital, Yogyakarta.Method. Observational descriptive and analytical study with cross-section design was performed. Subjects were recruited used a consecutive sampling method for subjects who met the inclusion and exclusion criteria. The statistical analysis used to find a correlation between the levels of the thyroid hormone and the performance of the functional mobility by Pearson Correlation test. Here the study used Spearman Correlation test if the conditions were not met the criteria. Significance limit with p < 0.05.Results. A total of 36 research subjects who met the inclusion and exclusion criteria. The mean age was 69.67±6.164 years. Consisted of 16 (44.4%) male and 20 (55.6%) were female. The median of TSH (Thyroid Stimulating Hormone) was 1.170 (0.19-3.64) μIU/mL and the median free T was 1.280 (0.80-2.34) ng/dL. TSH level in male was more than female with same time in gait speed. The male median TSH level was 1.370 (0.60-3.64) μIU/mL and women 0.980 (0.19-3.17) μIU/mL. Slow gait speed more than thirty second (high risk of falling), the TSH mean in mas was 2.690 μIU/mL and women 1.150 μIU/mL. The test results indicate thyroid hormone level has no significant effect on functional mobility performance (timed up and go test score) in the elderly subjects (p value=0.531) and with level Free T4 (p value=0.721).Conclusion: In this study population, thyroid hormones did not have a statistically significant correlation with functional mobility in the elderly. Males with higher serum levels and females with lower serum TSH (Thyroid Stimulating Hormone) were at increased risk of frailty.